2010
DOI: 10.1007/s00467-010-1455-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary proteome analysis identifies infants but not older children requiring pyeloplasty

Abstract: One out of every five children suffering from ureteropelvic junction obstruction (UPJO) requires pyeloplasty. This prevalence indicates an urgent necessity to identify high-grade UPJO as early as possible to avoid renal damage. A novel non-invasive proteomic urine test has recently been introduced that is able to detect these patients at an early stage. In the study reported here, we tested this approach to assess its use in our centre and to expand its application to older children. Twenty-seven children (med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 20 publications
0
30
0
4
Order By: Relevance
“…Using urinary peptidome analysis, we identified and validated a urinary peptide panel that predicted the clinical outcome of newborns with UPJ obstruction with 97% accuracy several months in advance (3,10). An independent small-scale study confirmed the efficiency of this biomarker panel (7). These studies indicate the potential of urinary proteomics to predict the clinical fate of patients with UPJ obstruction.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Using urinary peptidome analysis, we identified and validated a urinary peptide panel that predicted the clinical outcome of newborns with UPJ obstruction with 97% accuracy several months in advance (3,10). An independent small-scale study confirmed the efficiency of this biomarker panel (7). These studies indicate the potential of urinary proteomics to predict the clinical fate of patients with UPJ obstruction.…”
mentioning
confidence: 61%
“…Targeted strategies including urinary cytokine expression analyses failed to clearly determine the need for surgery in UPJ obstruction (3,4). On the other hand, untargeted strategies have been more successful and by using urinary proteomics, biomarkers for renal and non-renal diseases have been identified (5)(6)(7)(8)(9). Using urinary peptidome analysis, we identified and validated a urinary peptide panel that predicted the clinical outcome of newborns with UPJ obstruction with 97% accuracy several months in advance (3,10).…”
mentioning
confidence: 99%
“…In conclusion, the article by Drube et al [6] validates the proteomic approach in a small number of patients with unilateral UPJO in whom the analysis is performed at <1 year of age. It is not clear from this study why the sensitivity deteriorates in patients >1 year of age.…”
mentioning
confidence: 85%
“…Drube et al (this issue [6]) from the Department of Nephrology at Children's Hospital in Hannover obtained urinary specimens from patients with various grades of UPJO during the course of routine clinical care and shipped them to a commercial diagnostic company which distributes the test originally described by Decramer et al [3]. In six patients <1 year of age, the CE-MS analysis correctly classified five as needing surgery based on diuresis renography criteria, thereby confirming the validity of this approach in this pilot project.…”
mentioning
confidence: 98%
“…These include gestational age at diagnosis (Hutton et al, 1994); the volume of amniotic fluid (Oliveira et al, 2000;Sarhan et al, 2008); the presence of megacystis (Oliveira, et al, 2000); the appearance of the renal parenchyma on prenatal ultrasound Robyr, et al, 2005;Sarhan, et al, 2008); fetal urinary sodium, calcium, 2-microglobulin, and other urinary solutes and proteins (Decramer et al, 2008;Morris et al, 2007). Additionally, pilot studies show that urine proteome analysis can identify urodynamically significant UPJ obstruction in infants with hydronephrosis with a sensitivity of 83% and a specificity of 92%, although the test had poor diagnostic accuracy in patients older than 1 year of age (Drube et al, 2010). Although several of these markers and tests show promise as diagnostic or prognostic tools, no consensus yet exists as to the best panel of biomarkers to assess congenital obstructive nephropathy.…”
Section: Prospective Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%